Re(searching) the Truth About Our Criminal Justice System: Some Challenges1. (18th September 2017) - Ruane, Janet M.
Abstract : This article considers the current face‐off between "facts vs. alternative facts" as it relates to research on lethal encounters between police and minority citizens. I begin by reviewing major measurement challenges for those studying lethal police shootings and potential improvements for how we document police shootings. I also consider the increasing reliance on use of body cams and surveillance videos for what they may (or may not) bring to improving documentation of police/citizen encounters. Next I address a larger issue that provides the context for the "facts vs. alternative facts" dilemma: science's loss of standing as the recognized superior way of knowing about the world. Growing distrust in science, special interest research, paradigm shifts, and science illiteracy are all considered as reasons for the slippage of science as a credible knowledge source. Additionally, key traits of science (i.e., its inherent skepticism and tentative stance) may actually support the all‐too‐popular view that science no longer has an edge in producing valid and reliable information. I make a case for the need to reform what some see as a broken culture of science and for social researchers to commit to a serious agenda of replication of studies and findings.